Molecular Structure, Homo-Lumo and Vibrational Analysis Of Ergoline By Density Functional Theory - Joshi, Bhawani Datt; Thakur, Ghanshyam; Chaudhary, Manoj Kumar (Scientific World, 2021)
In this work, quantum chemical study on a natural product ergoline has been presented using density functional theory (DFT) employing 6-311++G(d,p) basis set. A complete vibrational assignment has been performed for the theoretical FT-IR and Raman wavenumbers along with the potential energy distribution (PED) with the result of quantum chemical calculations. The structure–activity relationship has been interpreted by mapping electrostatic potential surface (MEP). Graphical representation of frontier molecular orbitals with their energy gap have been analyzed theoretically for both the gaseous and solvent environment employing time dependent density functional theory (TDDFT) employing 6-31G basis set.